Isolated cryptococcal osteomyelitis in the setting of immune reconstitution inflammatory syndrome - Pamela Horton Embrey; Alexandra Long; Rasha Alfattal; Suimin Qiu; Joseph Patrik Hornak (Therapeutic Advances in Infectious Disease, 2024)
Cryptococcal infections, though rare, must be considered in all immunocompromised patients. Patients with HIV/AIDS on antiretrovirals may have a treatment course complicated by immune reconstitution inflammatory syndrome. Here we present a case of a 38-year-old woman with HIV/AIDS with knee pain who only began to experience severe pain after induction of antiretroviral therapy. She was found to have cryptococcal osteomyelitis without dissemination to the central nervous system, an unusual presentation for immunocompromised patients. She was treated with oral fluconazole with a resolution of symptoms. This case report suggests conservative management of isolated cryptococcal infection with fluconazole, regardless of immune status.